Ultrafast and low temperature laser annealing for crystalline TiO2 nanostructures patterned by electro-hydrodynamic lithography - Cha, S; Lee, S; Jang, J; Jang, A; Hong, J; Lee, J; Sohn, J; Kang, D; Kim, J (2013)
Direct patterning of inorganic materials based on electro-hydrodynamic lithography (EHL) has attracted tremendous attentions as next generation soft-lithography technologies owing to its simple and cost-effective process. We show that the EHL technique based nanoscale inorganic pattern transfer coupled with ultrafast laser annealing is suitable for obtaining nanostructured TiO 2 over a large area with great fidelity. The laser annealing technique enables us to overcome a technical issue of EHL associated with long processing time and high annealing temperature. We further demonstrated the enhanced switching performance by using the laser annealed TiO2 layer as an electron transport layer in the electro-chromic device. © 2013 AIP Publishing LLC.